Assessment of the Efficiency of Thermal Waste Regeneration in the Blown Impassable Channels of Heating Mains - V. A. Sednin; T. V. Bubyr (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
To solve the problem of increasing the energy efficiency of thermal networks with heat pipelines located in impassable channels, a schematic and structural solution for the rational utilization of thermal waste generated during the transport of thermal energy has been developed. Due to the complexity of creating a full-scale experimental installation, a virtual experimental installation created by means of the Ansys software package was used in the study, on which an active numerical experiment was performed. Regression equations have been obtained for calculating the intensity of heat transfer from pipelines and channel enclosing structures with a given change in the size, length of channels and pipelines for various outdoor and ground temperatures characteristic of the heating and inter-heating periods. Statistical analysis, verification and validation of the obtained regression correlations were carried out, two-dimensional hypersurface crossections were obtained in the studied range of controlled factors. The results of numerical simulation of the operating modes of forced ventilation of impassable channels of heating mains with determination of the density of heat flows from the ground and mains water pipelines, air flow and the corresponding exhaust fan capacities have been presented. The following conditions in this case were accepted: the air flow rate is not higher than 8 m/s, the length of the heat pipeline section ensures the air temperature at the outlet of the channel at which there is no increase in heat losses from mains water pipelines to the ground under normal operating conditions of heating networks. The energy efficiency of heat utilization dissipated by mains water pipelines as well as ground cooling in impassable heating mains channels was investigated by intensifying their ventilation and using heat pump equipment at the end points of the channels for heating mains water, depending on the geometric characteristics of the heating mains section, air temperature, soil and mains water installations at central heating points or directly at heat sources. The potential of energy saving for district heating systems with various types of heat sources and the combined power system during the utilization of heat flows from the ground and heat pipelines laid in impassable channels has been identified. On the basis of the energy-saving potential, a technical and economic assessment was carried out and the conditions for the economic feasibility of implementing the proposed technical solution were determined.